THE ANALYSIS OF STRUCTURE SHIFT IN TRANSLATING LOCATIVE PREPOSITIONAL PHRASE INTO INDONESIAN - Susana, Kadek Yogi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
This research is mainly aimed to analyze the structure shift of locative prepositional phrase and its equivalences in Indonesian. The data of this study was taken from the biography of Steve Jobs. This book is published in English as the source language and in Indonesian as the target language. It is only the structure shift of locative prepositional phrase using preposition ‘at’, ‘in’, and ‘from’ is analyzed. The research is done through note taking technique in order to find and collect some data. In analyzing the data, translational identity method was applied that people use for comparing between one language with other language to find and analyze the equivalence (Sudaryanto, 1993). The main theory used to analyze the structure shift in translation of the biography of Steve Jobs is Translation Shift proposed by Catford (1965). The finding shows that the translation shift in this structure shift affects the process of translating locative prepositional phrase. Loss and gain information occurs in the process of translation from source language into target language.
Keywords: structure shift, translation, source language, target language.